POLITIK HUKUM PEMBERLAKUAN GELAR â€œSARJANA HUKUMâ€ UNTUK ALUMNI JURUSAN HUKUM BISNIS SYARIAH - Yasin, Mohamad Nur (Jurisdictie: Jurnal Hukum dan Syariah, 2016)
The national education system implement in Indonesia in the frame of legal positive. The quality of education out put must be measured legally with giving an academic degree. The academic degree earned by fresh graduate of Sharia Business and Economic Law (Muamalah) Department changed from Doctorandus/ Doctoranda (Drs/Dra), Sarjana Agama (S.Ag.), Sarjana Hukum Islam (SHI), Sarjana Syariah (S.Sy), and Sarjana Hukum (SH). The changes of degree from SHI/S.Sy to SH is contains a meaning of legal politic. This paper focus on two problems (a) what about legal politic of the degree of SH, (b) what the degree of SH can be ideal solution for fresh gradute of Sharia Business and Economic Law (Muamalah) Department. By using normative law studies, there are two findings. First, legal politic of the degree of SH consist of (a) the politic of legal formulation, namely the formulation of degree of SH be done in top down and buttom up, (b) the politic of legal substance, empowering spirit of knowledge integration and institution, and (c) the politic of legal enactment show that there are contra-justisia and miss-undertanding under perspevtive of magister program of law management and steakholders. Second, the admissibility of fresh graduate of Sharia Business Law (Muamalah) Department to law sector should not automatically in tandem with degree of SH.